Who Owns the Data? Open Data for Healthcare - Kostkova, Patty; Brewer, Helen; de Lusignan, Simon; Fottrell, Edward; Goldacre, Ben; Hart, Graham; Koczan, Phil; Knight, Peter; Marsolier, Corinne; McKendry, Rachel A.; Ross, Emma; Sasse, Angela; et al. (Frontiers in Public Health, 2016)
Research on large shared medical datasets and data-driven research are gaining fast momentum and provide major opportunities for improving health systems as well as individual care. Such Open Data can shed light on the causes of disease and effects of treatment including adverse reactions side-effects of treatments, while also facilitating analyses tailored to an individual individual’s characteristics, known as personalised or “stratified medicine”. Developments such as crowdsourcing, participatory surveillance, individuals pledging to became ‘data donors’ and the ‘quantified self’ movement (where citizens share data through mobile device-connected technologies) have great potential to contribute to our knowledge of disease, improving diagnostics and delivery of healthcare and treatment. However, alongside the clear potential, there are also concerns over privacy, confidentiality, and control of data about individuals once it is shared. Issues such as user trust, data privacy, transparency over the control of data ownership, and the implications of data analytics for personal privacy with potentially intrusive inferences are becoming increasingly scrutinised at national and international levels. This can be seen in the recent backlash over the proposed implementation of care.data, which enables individuals’ NHS data to be linked, retained, and shared for other uses, such as research and, more controversially, with businesses for commercial exploitation. By way of contrast, through increasing popularity of social media, GPS-enabled mobile apps and tracking/wearable devices, the IT industry and MedTech giants are pursuing new projects without clear public and policy discussion about ownership and responsibility for user-generated data. In the absence of transparent regulation this papers